Screening of fungi on solid state bioconversion of oil palm empty fruit bunch for production of cellulase - Abdul Karim, Mohamed Ismail; A. Hamid, Manisya Zauri; Yusof, Faridah; Alam, Md. Zahangir (IIUM Press, 2011)
Five potential strain of fungi (Trichoderma reesei RUT C-30 (ATCC 56765, USA; Trichoderma harzanarium (SCahmT 105); Trichoderma harzianum (Isolated by UPM); Penicillium 1 (isolated from sewage treatment plant);Peniczllium 2 (isolated from empty fruit bunch) were screened for production of cellulase using solid state bioconversIOn of oil palm empty fruit bunch. Hydrolytic activities of strains were tested on carboxymethylcellulose (CMC) agar. Strain Penicillzum 2 (P 2) showed the highest radius of hydrolytic activity of 1.2 cm. This was followed by T. reesez RUT C-30 (RUT C-30) and isolated Peniczllium 1 (P 1) with radius clearance of 1.0 and 0.9 cm, respectively. These strains of culture (Ix 107 spores/ml ) were seeded in oil palm empty fruit bunch (70% moisture) supplemented with 1N of potassium dihydrogen phosphate and 1N of potassium hydrogen phosphate in shake flask experiment which was fermented for 8 days at 30°C for production of cellulase. Result obtained indicate T. reesei RUT C-30 produce the highest CMCase (1.831 U/gds) at day 6 of fermentation. For FPase Trichoderma harzianum gave high production (0.156 U/gds at 4 days fermentation. Penicillium 1 produced the highest ~-glucosidase of 2.361 U/gds at day 2fermentation.